O ensino de química na educação básica no contexto da experimentação investigativa e da aprendizagem significativa - (:unkn) unknown (Universidade Estadual de Goiás, 2024)
Education in Brazil has been experiencing intense debate and discussion, especially with theNational Common Core Curriculum (BNCC) which, after a long time in the making, has beenimplemented in recent years. Specifically in secondary education, much has been said aboutthe need to promote an education that allows students to recognize in their daily lives what istaught in the classroom. For the teaching of chemistry in basic education, new approacheshave been devised, discussed, proposed and even applied, with the aim of identifying betterways of improving the teaching-learning process. In this context, inquiry-based teaching andexperimentation are presented in the literature as alternatives for chemistry classes. Thus, thisdissertation was based on the question “How can Inquiry-based Teaching Sequence andexperimentation be used in high school in order to promote meaningful student learning?”.The general objective was to understand the potential and limitations of using Inquiry-basedTeaching Sequence and experimentation in secondary education, with a focus on promotingmeaningful student learning. To meet the proposed objective, the dissertation was organizedinto five chapters. Chapters 01 and 02 involved a literature review and systematic review ofthe literature in order to understand the research topic. Chapter 03 involved collecting datafrom teachers at a regional school in the state using a questionnaire and analyzing GroundedTheory. Chapter 04 covers the Inquiry-based Teaching Sequence (SEI) that were constructedbased on the theoretical framework presented throughout the dissertation. The final chapterpresents the results of applying the SEIs in a real teaching-learning context. A qualitativeapproach was used to analyze the data, with a focus on understanding the potential of SEIs.Five SEIs were developed to make up the Educational Product, which aimed to encompassteaching by investigation and experimentation in chemistry teaching, with a focus onmeaningful learning for high school students. Of the five SEIs, two were designed for chemistryclasses in the 1st grade of secondary school, two for the 2nd grade and one of the sequencesis aimed at students in the 3rd grade of secondary school. The SEIs were validated in a realteaching context in a state public school in the interior of Goiás with 258 students from thethree high school grades. The validation of the Educational Product was essential for itsimprovement and it is hoped that it will be used by other teachers who can adapt theproposals to help them.
Teaching chemistry in basic education in the context of investigative experimentation and meaningful learning
Keywords: Ensino de química; Experimentação investigativa; Aprendizagem significativa; Chemistry teaching; Investigative experimentation; Meaningful learning; EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS EXATAS E DA TERRA::QUIMICA